Prognostic value of prognostic nutritional index in patients with ovarian cancer: a systematic review and meta-analysis - Zang, Tao; Huang, Bintao; Wang, Qinggao (Frontiers in Oncology, 2026)
BackgroundAccumulating evidence indicates an association between the prognostic nutritional index (PNI) and prognosis in patients with ovarian cancer (OC). However, the conclusions drawn from current studies remain controversial.MethodsWe performed a systematic literature search in PubMed, Embase, Web of Science, and the Cochrane Library, covering the period from each database’s inception up to July 8, 2025, to identify studies investigating the relationship between PNI and clinical outcomes. Eligible studies were identified and selected based on predefined inclusion and exclusion criteria. Primary outcomes included progression-free survival (PFS), overall survival (OS), cancer-specific survival (CSS), and disease-specific survival (DSS), which were quantified using hazard ratios (HR) with their respective 95% confidence intervals (CI).ResultsWe analyzed thirteen cohort studies involving 5,129 patients. Meta-analysis findings demonstrated an association between reduced PNI and poorer PFS (HR = 1.59, 95% CI: 1.24–2.03; p=0.0002) and curtailed OS (HR = 1.72, 95% CI: 1.36–2.18; p<0.00001), whereas no such correlation was observed in the DSS (HR = 1.88, 95% CI: 0.70–5.10; p=0.21) and CSS (HR = 1.91, 95% CI: 0.81–4.52; p=0.14) analyses.ConclusionA low PNI is associated with shortened OS and PFS in OC patients. PNI thus serves as a robust biomarker for prognostic evaluation in this patient population, providing meaningful implications to guide clinical decision-making in the context of OC.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251116811, identifier CRD420251116811.